If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 + 4x + -5 = 90 Reorder the terms: 4 + -5 + 9x + 4x = 90 Combine like terms: 4 + -5 = -1 -1 + 9x + 4x = 90 Combine like terms: 9x + 4x = 13x -1 + 13x = 90 Solving -1 + 13x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 13x = 90 + 1 Combine like terms: -1 + 1 = 0 0 + 13x = 90 + 1 13x = 90 + 1 Combine like terms: 90 + 1 = 91 13x = 91 Divide each side by '13'. x = 7 Simplifying x = 7
| (5x+12)+(8x-5)= | | 9v-43=2(v+3) | | w/15.36=6 | | (x-4)=13 | | -7x-87=-14x+39 | | 18x=48+12x | | -4*-4*-4=x | | 5x-10+2x+9=90 | | 4x1/12 | | 14.3-.4x=2.6+5.6 | | 5+2(3t-7)=3(2t+5)-24 | | f-1(30)=(4x-3)/2 | | 5x-10+2x+9=270 | | 7(4x+6)+11= | | 42a-22=-4(1-6a) | | -7*-7=x | | 7(4c+6)+11= | | 12x-1=6x+16 | | 3(x^2-1)=8x | | -3-4y=17 | | -4-18=-2(u-6) | | -x-89=177-8x | | 4(v-8)-8v=-28 | | 3y-10=y+30 | | y=12(0.85)x | | -2/3x-9/7=-1/2 | | -3x(2x+5)=-4(-x+2) | | 11x+3-5x= | | -x(13+4x)=-3(5-9x)+2 | | (7x+2)+(18-7x)= | | r^3+4r^2=0 | | -115+x=9x+93 |